Etika Komunikasi dalam Islam : Analisis terhadap Konsep Tabayyun dalam Media Sosial - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Hilmi Khoiri Thohir; Natasha Aurelia Ramadhani; Rosya Ahya Sabilaa (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Communication ethics in Islam plays a crucial part in forming reasonable and stately social interactions. One of the basic standards of Islamic communication morals is the concept of tabayyun, which refers to the clarification or confirmation of data some time recently it is spread. This concept gets to be profoundly significant within the setting of social media utilize, which has ended up far reaching in society. Social media, with its ease and speed of data spread, regularly serves as a channel for unsubstantiated news, which can lead to defame or errors. This ponder points to analyze the application of the tabayyun guideline in social media communication from an Islamic perspective. The approach utilized in this think about could be a writing audit, looking at essential sources such as the Qur'an, Hadith, and related academic writing. The examination comes about appear that tabayyun plays an basic part in keeping up truth and anticipating the spread of untrue data that may hurt people or bunches. On social media, the tabayyun rule can be actualized by confirming gotten data, looking for dependable sources, and dodging the rushed spread of unsubstantiated data. This consider concludes that Islamic communication morals through tabayyun can contribute emphatically to making a more mindful and serene advanced communication environment.